2009
DOI: 10.1002/cncr.24159
|View full text |Cite
|
Sign up to set email alerts
|

Association of marijuana use and the incidence of testicular germ cell tumors

Abstract: Background-The incidence of testicular germ cell tumors (TGCT) has been increasing the past 4-6 decades, but exposures accounting for this rise have not been identified. Marijuana use has also grown over this time period, and chronic marijuana use produces adverse effects on the human endocrine and reproductive systems. We tested the hypothesis that marijuana use is a risk factor for TGCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
127
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(143 citation statements)
references
References 79 publications
10
127
0
2
Order By: Relevance
“…5 Finally, and perhaps most convincingly, the study by Daling et al demonstrated that the risk of developing NTGCT was elevated for subjects who started using marijuana at age 18 years or younger, but it was not found to be elevated for those who started using marijuana after age 18 years. 2 If these data are available to be analyzed from the current study, it would be useful to know whether the results corroborate the findings of Daling et al regarding the impact of age at the time of first marijuana use on the development of NTGCT.…”
supporting
confidence: 74%
“…5 Finally, and perhaps most convincingly, the study by Daling et al demonstrated that the risk of developing NTGCT was elevated for subjects who started using marijuana at age 18 years or younger, but it was not found to be elevated for those who started using marijuana after age 18 years. 2 If these data are available to be analyzed from the current study, it would be useful to know whether the results corroborate the findings of Daling et al regarding the impact of age at the time of first marijuana use on the development of NTGCT.…”
supporting
confidence: 74%
“…Daling et al conducted the initial case-control study reporting a 70% increased risk of non-seminoma and mixed histology testicular germ cell tumours among current marijuana (especially among users who started in adolescence) compared to matched controls (odds ratio [OR] 2.3; 95% confidence interval [CI] 1.3-4.0). 4 This initial data was further supported by a recent systematic review and meta-analysis conducted by Gurney et al, which included three case-control studies between 198 and 2015, including a total of 719 cases of testicular germ cell tumours along with 1419 controls. 2,21,22 This study further reinforced the findings of the 2009 case-control study suggesting that current cannabis use at least once weekly or for a long duration (>10 weeks) is associated with the development of testicular germ cell tumour (OR 1.62; 95% CI 1.13-2.31), with the strongest association for non-seminoma tumours.…”
Section: Cannabinoids and Testicular Cancermentioning
confidence: 89%
“…The first hypothesis speculates that since endocannabinoids are degraded by fatty acid amid hydrolase while THC is mainly metabolized by cytochrome P 450 enzymes with a half-life of four days in chronic marijuana users, the prolonged activation of CB1 and CB2 in marijuana users can disrupt the normal antitumour activity of the ECS. 4 The second hypothesis is related to the hypothalamus-pituitarytesticular axis. THC typically acts by activating the CB1 and CB2 receptor in the brain to induce a "high."…”
Section: Cannabinoids and Testicular Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, this statement was recently challenged by a study performed by Aldington and colleagues, [176] which showed that cannabis smoking increased the risk for lung cancer, but it is not certain that cannabinoids are responsible for this correlation. [177] Along the same lines, it is not clear whether chronic marijuana use is correlated with an increased incidence of testicular germ cell tumours [178] because of cannabinoid action. An increasing amount of data shows attenuation of tumour growth by both orally and locally administered cannabinoids in different animal models, raising high hopes for potentially new treatments, in particular in combination with established chemotherapeutic agents (vide supra).…”
mentioning
confidence: 99%